Pengaruh Pertumbuhan Tanaman Terong Ungu (Solanum melongena L.) terhadap Media dan Jarak Tanam yang Berbeda - Linda Piliang; Rahmadina Rahmadina (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
The purpose of this study is to be able to explain how growing media and spacing affect purple eggplant's vegetative growth responses. In this investigation, two treatments with six replications each were employed in a randomized block design (RBD). F1: J1 = 30 x 40 cm and D2 = 50 x 60 cm are the two levels of spacing. F2: There are two levels for using planting media: M1 = soil + sand 2: 1 and M2 = soil + cocopeat 2: 1. Plant height measurements, tests for the chlorophyll a and b leaf area indices, and relative growth rates as well as total and net assimilation rates were the variables employed in this study. The study's findings recommend using planting media with the best level of M2 = soil + cocopeat for plant height criteria. The ideal level for spacing the parameters for the chlorophyll test and the rate of net assimilation is J2 50 x 60 cm. According to the research, the planting medium and spacing, particularly on the variables of plant height, chlorophyll test, and net assimilation rate, have a substantial impact on the vegetative growth of purple eggplant.